2004
DOI: 10.1669/0883-1351(2004)019<0170:teopat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomic Effects of pH and Temperature on Extant Avian Dinosaur Eggshell

Abstract: Avian and non-avian dinosaur eggshell contains clues that are helpful in the reconstruction of ancient habitats and behaviors. Fossilized eggshell often shows signs of corrosion attributed to acid dissolution of the calcium carbonate, but this process has never been quantified in controlled experiments. In work reported here, extant avian dinosaur eggshell fragments were placed in buffered solutions of varying pH and temperature for varying periods of time. Changes in the appearance, mass, surface area, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
1
31
0
4
Order By: Relevance
“…The classifiable eggshell fragments were largely well preserved with distinct ornamentation and microstructural characteristics. They occasionally show different degrees of mechanical and/or chemical surface erosion and densely spaced pits and pinholes of variable sizes which seem to be traces of acidic erosion caused by bacterial activity (Smith and Hayward 2010) and/or by the inorganic chemical environment (Bravo et al 2003;Clayburn et al 2004). Based on gross morphology, more than 99% of the classifiable eggshell fragments could be grouped into three different morphotypes with very different relative abundances and a considerable diversity in ornamentation within two of the three groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The classifiable eggshell fragments were largely well preserved with distinct ornamentation and microstructural characteristics. They occasionally show different degrees of mechanical and/or chemical surface erosion and densely spaced pits and pinholes of variable sizes which seem to be traces of acidic erosion caused by bacterial activity (Smith and Hayward 2010) and/or by the inorganic chemical environment (Bravo et al 2003;Clayburn et al 2004). Based on gross morphology, more than 99% of the classifiable eggshell fragments could be grouped into three different morphotypes with very different relative abundances and a considerable diversity in ornamentation within two of the three groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Carpenter (1982) discussed the effect of local pH on the preservation potential of dinosaur eggshell and found that in 60 days acids produced by decaying vegetation dissolved the broken edges of chicken eggshell fragments. Clayburn et al (2004) examined this effect further, along with that of temperature, in controlled experiments with glaucous-winged gull (L. glaucescens) eggshell fragments. Treatment in buffered solutions of varying pH and temperature for up to 42 days resulted in corrosion and pitting of the outer surface and corrosion on the mammillary layer of the inner surface.…”
Section: Previous Workmentioning
confidence: 99%
“…Unfortunately, these delicate microstructures are the focal point of study. As reported by Clayburn et al (2004), the survivability of calcium carbonate is dependent on the absence of water. In fact, weathered paleontological samples often exhibit no presence of a mammillary layer (Robert Pierce 2005, personal communication).…”
Section: Avian Embryogenesismentioning
confidence: 61%
“…Taphonomy and eggshell is a concern that has been addressed to some degree within the field of paleontology. Clayburn et al (2004) conducted a series of controlled experiments on avian eggshell in order to better understand the taphonomic effects of pH and temperature. In this study, avian eggshell was naturally weathered for 1e2 years in a surface context, as well as in a laboratory setting for a period of days to months.…”
Section: Avian Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation